2024
DOI: 10.14336/ad.2023.0524
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Gut-Microbiota Axis in Amyotrophic Lateral Sclerosis: A Historical Overview and Future Directions

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a devastating neurodegenerative disease which is strongly associated with age. The incidence of ALS increases from the age of 40 and peaks between the ages of 65 and 70. Most patients die of respiratory muscle paralysis or lung infections within three to five years of the appearance of symptoms, dealing a huge blow to patients and their families. With aging populations, improved diagnostic methods and changes in reporting criteria, the incidence of ALS is likely to show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 166 publications
(224 reference statements)
0
2
0
Order By: Relevance
“…Initial studies of the microbiome in ALS consistently found dysbiosis to be present, both through potentially harmful bacterial overgrowth and through the reduced biodiversity of potentially beneficial bacterial strains. These studies proposed that pro-inflammatory dysbiosis might stem from microbial imbalance, compromising the intestinal epithelial barrier and triggering immune/inflammatory responses, thus playing a role in ALS pathogenesis [46]. Patients with ALS who exhibit heightened richness and diversity in their microbiome, along with a higher Firmicutes to Bacteroidetes ratio, are noted to face a heightened risk of premature mortality [47], this association being observed at a later stage in disease progression.…”
Section: Microbiome Alterations In Alsmentioning
confidence: 99%
“…Initial studies of the microbiome in ALS consistently found dysbiosis to be present, both through potentially harmful bacterial overgrowth and through the reduced biodiversity of potentially beneficial bacterial strains. These studies proposed that pro-inflammatory dysbiosis might stem from microbial imbalance, compromising the intestinal epithelial barrier and triggering immune/inflammatory responses, thus playing a role in ALS pathogenesis [46]. Patients with ALS who exhibit heightened richness and diversity in their microbiome, along with a higher Firmicutes to Bacteroidetes ratio, are noted to face a heightened risk of premature mortality [47], this association being observed at a later stage in disease progression.…”
Section: Microbiome Alterations In Alsmentioning
confidence: 99%
“…The MGB axis includes neural signal networks, immune signal networks, and chemical signal networks ( 60 , 61 ). First, through the regulation of intestinal peristalsis by the autonomic nervous system, the brain’s exogenous parasympathetic and sympathetic nerves influence the activity of the internal intestinal neuron network, thereby regulating intestinal peristalsis and the rate of content transport ( 62 ). Secondly, the central efferent nerve of the brain, directly or through the enteric nervous system, is in contact with the intestinal secretory cells, regulating the secretory substances of the luminal cells, directly acting on the microbiome, and regulating microbial host signaling.…”
Section: Fmt In Alleviating Depression Via Microbial-gut-brain Axismentioning
confidence: 99%